2008
DOI: 10.1093/europace/eun005
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of Wolff-Parkinson-White syndrome with right septal or posteroseptal accessory pathways on cardiac function

Abstract: Wolff-Parkinson-White syndrome with right septal or posteroseptal accessory pathways may cause LV dyssynchrony and jeopardize global LV function. Radiofrequency catheter ablation resulted in normalized QRS duration, mechanical resynchronization, and improved LV function. Even in the absence of arrhythmias, RFA of right septal or posteroseptal pathways may be considered in patients with significantly decreased LV function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
110
1
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(126 citation statements)
references
References 35 publications
7
110
1
8
Order By: Relevance
“…Interestingly, left ventricular dysfunction because of abnormal ventricular activation has been found to be fully reversible in pediatric patients, either spontaneously, due to loss of preexcitation, or by ablation. 26 However, whether left ventricular dysfunction, and thereby potentially HF, as a result of preexcitation is fully reversible in adult patients remains elusive. A recent study using ECGgated cardiac computed tomography on adult patients with WPW suggested irreversible myocardial damage reflecting long-term effects of dyskinesia.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, left ventricular dysfunction because of abnormal ventricular activation has been found to be fully reversible in pediatric patients, either spontaneously, due to loss of preexcitation, or by ablation. 26 However, whether left ventricular dysfunction, and thereby potentially HF, as a result of preexcitation is fully reversible in adult patients remains elusive. A recent study using ECGgated cardiac computed tomography on adult patients with WPW suggested irreversible myocardial damage reflecting long-term effects of dyskinesia.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that patients with right septal or postero-septal accessory pathways presented with abnormal intraventricular septal wall motion, as compared with left-sided accessory pathways that resulted in abnormal LV posterior wall motion. 13) Left ventricular wall motion and the degree of dyssynchrony most likely are dependent upon the location of the accessory pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been some reports of decreased cardiac function in patients with WPW in the absence of SVT, and these patients (most of whom were infants or children) tend to exhibit segmental dyskinesia of the myocardium and/or global LV dysfunction. [7][8][9][10][11] Pre-existing areas may lead to dyssynchrony in LV motion and result in global LV dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In those reports, most patients exhibited right septal or posteroseptal accessory pathways. [7][8][9][10][11] with WPW syndrome with a right-sided free-wall accessory pathway and dilated cardiomyopathy (DCM), in which LV function improved following RF ablation. 12) In patients with decreased LV cardiac function, such as those with DCM, LV dyssynchrony can further compromise cardiac function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation